The Influence of Ready-To-Eat Food Consumption Behavior on the Risk of Hypertension Among Adolescents at SMK Perguruan Rakyat 2 Jakarta - Selviana Selviana; Nurni Nurmaliyati (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Ready meals are also known as types of food that are made in a practical and fast way that are not nutritious. Consuming junk food can also interfere and damage health as it can cause diabetes mellitus, hypertension, coronary heart disease, and cancer. The purpose of conducting this study was to determine the effect of consumption behavior of ready-to-eat foods on the risk of hypertension. Data collection by distributing questionnaire sheets, this research design is descriptive with a cross sectional approach. Based on bivariate tests regarding the relationship between hypertension and consuming junk food, it was found that there were 11 and Yes (knowing) about hypertension (61.1%) and there were 7 respondents who consumed junk food with 38.9% results. There were 11 respondents who did not understand about hypertension with a score (50.0%) and who did not consume junk food there were 19 respondents (45%). From the results of bivariate analysis obtained p value = 0.002 (< 0.05) thus it can be said that there is a significant relationship between junk food diet and hypertension. From the results of this study, it is expected for all students and students of grade X and XI of Smk Perguruan Rakyat 2 to be able to change a healthy lifestyle by not consuming ready-to-eat   ABSTRAK Makanan siap saji juga dikenal sebagai jenis makanan yang dibuat dengan cara yang praktis dan cepat yang tidak bergizi. Mengkonsumsi junk food juga dapat mengganggu dan merusak kesehatan seperti dapat menyebabkan diabetes mellitus, hipertensi, penyakit jantung koroner, dan kanker. Tujuan dalam melakukan penelitian ini adalah untuk mengetahui pengaruh perilaku konsumsi makanan siap saji terhadap resiko penyakit hipertensi. Pengambilan data dengan menyebarkan lembar kuesioner, desain penelitian ini adalah deskriktif dengan pendekatan cross sectional. Berdasarkan uji bivariat mengenai hubungan hipertensi dengan mengkonsumsi junk food didapatkan bahwa yang mengerti tentang hipertensi ada 11 dan Ya (mengetahui) tentang hipertensi ( 61,1%) dan  ada 7 responden  yang  mengkonsumsi junk food  dengan hasil 38,9%. ada 11 responden yang tidak mengerti tentang penyakit hipertensi dengan nilai (50,0%) dan yang tidak mengkonsumsi junk food ada 19 responden ( 45%). Dari hasil analisis bivariat diperoleh nilai p value = 0,002 (< 0,05 ) dengan demikian dapat dikatakan bahwa ada hubungan yang signifikan antara  pola makan junk food dengan hipertensi. Dari hasil penelitian ini, diharapkan bagi seluruh siswa dan siswi kelas X dan XI Smk Perguruan Rakyat 2 untuk dapat merubah pola hidup sehat dengan tidak mengkonsumsi makanan siap saji.